The Impact of Bullying in the Integral Development and Learning from the Perspective of Children in Preschool and School - María Ester Morales-Ramírez; Margarita Villalobos-Cordero (Universidad Nacional, Costa Rica, 2017)
This article is part of a wider investigation about the impact of bullying on the integral development and learning of preschoolers and schoolchildren. An objective was designed to allow "analyzing the impact of bullying in the integral development of preschool and schoolchildren to promote prevention and intervention strategies to address this problem." To achieve this, a study with a mixed approach, of exploratory and descriptive nature, was conducted to analyze the influence exerted in the learning and development of a child who experienced bullying. The information contained in the article only renders the answers related to the impact and provided by 857 children, namely: 237 preschoolers, 286 of the third grade and 334 of the fourth grade. We worked with these groups in order to detect if there were signs of bullying from preschool, and if there was any significant difference in the perception of this problem from students of the first and third cycle. We worked with 14 schools in the province of Heredia, Costa Rica, randomly selected, and coordinated with authorities and parents to obtain authorizations. To compile the information, a questionnaire was constructed, consisting of open and closed questions of yes and no answer. Also a semi-structured interview based on the designed questionnaire was applied to the children at the preschool level. The data were analyzed from a quantitative and qualitative perspective. This perspective included emerging categories elaborated from the answers provided by the children, to assure that their feelings and thoughts about bullying constitute an input to raise awareness of the prevailing need to prevent this problem and to address it in all the areas in which it is present. Among the most relevant results found, 229 students (26.7%) reported having been harassed; of these, 198 (86.5%) are actually suffering from bullying, since the time for suffering this harassment can vary from weeks to a year, with repeated episodes in a single day. Likewise, the greatest impact of this problem has been in the socio-emotional area, followed by an incidence in learning, mainly in motivation, because 29.2% openly expressed that they did not want to continue attending the school. The places for bullying against students are classrooms, hallways, school cafeterias, restrooms, out of school facilities, and during recess. In the opinion of the researchers, it is imperative that the educational center conducts a diagnosis with the entire student population allowing to determine the real incidence of this problem, to establish a constant supervision of the teaching staff with students under their responsibility, and to train the whole educational community, not only to raise awareness, but also to address bullying in a timely and effective manner within the existing legislation framework.